PERSEPSI AKUNTAN PERUSAHAAN DAN AKUNTAN PUBLIK TERHADAP KONSEP DASAR, PENGUKURAN DAN PENGUNGKAPAN AKUNTANSI LINGKUNGAN - ethika ethika; Widia Gesti Marda (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2021)
This study aims to empirically examine the differences in perceptions of corporate accountants and public accountants to basic concepts, measurements, and disclosures of environmental accounting. This research was conducted at Public Accounting Firms and Corporate Accountants in West Sumatera. Sampling in this study using the convenience sampling method, in order to obtain a sample of 60. the data analysis technique used to test the hypothesis is the Differential Test (Independent Sample T-test). The results of this study indicate that there is no difference in perceptions between corporate accountants and public accountants on the basic concepts of environmental accounting, environmental accounting measurements, and environmental accounting disclosures. Where both corporate accountants and public accountants have the same perception of the existence of the basic concepts of environmental accounting, environmental accounting measurements, and environmental accounting disclosures are currently inadequate. This research shows that it is necessary to establish as soon as possible special standards on environmental accounting, as a guideline in carrying out environmental accounting practices in companies considering the need for transparency of responsibility for the environment Keywords: Basic Concepts of Environmental Accounting, Environmental Accounting Measurements, and Environmental Accounting Disclosures.